2018
DOI: 10.1093/jscr/rjy018
|View full text |Cite
|
Sign up to set email alerts
|

Lymphangioma cavernous of the small bowel mesentery, an infrequent cause of acute abdomen in adult

Abstract: Lymphangioma is a benign mass lesion characterized by numerous thin-walled lymphatic spaces that usually manifests in the first few years of life. They generally appear in the head, neck and axillary regions. Abdominal lymphangiomas have been reported however they are rare 5%. The small bowel mesentery lymphangioma has been described in <1%. Lymphangiomas may remain asymptomatic or present with complications depending on the size and location of the lesion. We present a case of a 71-year-old female, she presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…The clinical features of a mesenteric lymphangioma can be rather non-specific. However, reports have documented abdominal pain, vomiting, abdominal distension, a palpable abdominal mass or an acute abdomen, which includes symptoms of bowel obstruction, volvulus, bleeding and infection 9 14…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The clinical features of a mesenteric lymphangioma can be rather non-specific. However, reports have documented abdominal pain, vomiting, abdominal distension, a palpable abdominal mass or an acute abdomen, which includes symptoms of bowel obstruction, volvulus, bleeding and infection 9 14…”
Section: Discussionmentioning
confidence: 99%
“…The primary and gold standard treatment of lymphangiomas is radical surgical excision even when patients are asymptomatic. This is due to their potential to grow enormously to invade adjacent structures and cause complications, as well as their potential to express malignant change, particularly if they are of the cavernous subtype 9 10. Complete resection is also necessary for diagnostic confirmation and recurrence prevention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Her episode of what was presumed to be biliary colic has the potential to be either an inciting, inflammatory event that led to the formation of her mass, or the first clinical presentation of her mass that was misdiagnosed at the time. In a 2018 case report, Rojas and Molina24 suggested that their patient’s small bowel mesentery cavernous lymphangioma may have been a result of her prior cholecystectomy, appendectomy or hysterectomy. Their report, as well as others,25 demonstrate surgery as a potential risk factor for the development of abdominal lymphangiomas, but it is unlikely that our patients open umbilical hernia repair caused any trauma at the transverse mesocolon mesentery.…”
Section: Discussionmentioning
confidence: 99%
“…This condition usually manifests in kids in their first few years of life . Over 95% of the lesions are found in the head, neck and axillary regions, and rarely could affect thoracic and abdominal cavities, where small bowel is involved in less than 1% . The symptoms vary from asymptomatic, mild abdominal pain or a mass in routine physical examination to fatal such as volvulus or involvement of the mesenteric arteries which may require emergency surgery.…”
mentioning
confidence: 99%